Factors related to the adoption of organic farming in Spanish olive orchards - Parra López, C.; Calatrava Requena, J. (Spanish Journal of Agricultural Research, 2005)
The area given over to the cultivation of organic olive trees in Spain has greatly increased in the last ten years. The diffusion of organic farming is desirable since its principles are in line with the aim of the current EU Common Agricultural Policy to harmonise agrarian production and environmental protection, and to encourage the production of quality agricultural goods. This paper characterises organic olive growers and farms in the south of Spain and compares them to their conventional counterparts. Information was gathered in a survey of 322 olive growers. The organic growers differed from their conventional counterparts in that their orchards were less productive and in the more part-time nature of their dedication to agriculture. They were also younger, more involved in management and administration of the holding, attended more courses, were more commonly members of agricultural associations, received more information via the Andalusian Committee for Organic Agriculture (a control, certification and training organization), had a more negative opinion regarding the use of chemicals, and believed that organic agriculture required more time and effort but provided greater returns.